Manfaat Media Pembelajaran YouTube terhadap Capaian Kompetensi Mahasiswa - Jenny Ramadona Putri Ardi Yudha; Sri Sundari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to analyze how the influence of YouTube learning media on student competency achievement. The method used is a systematic review of the PubMed, ProQuest and Google Scholar databases. The results showed that YouTube is one of the learning media used by students to improve competency achievement. In conclusion, YouTube as a learning medium is very influential in increasing knowledge, helping to get information about assignments, knowing the development of information, and can be used as material to deepen the material. Keywords: Student, Learning media, YouTube